Bacterial Protein Toll-Like-Receptor Agonists: A Novel Perspective on Vaccine Adjuvants - Kumar, Sudeep; Sunagar, Raju; Gosselin, Edmund (Frontiers in Immunology, 2019)
Adjuvants have been used in vaccines for over a century, still the search for safe and effective vaccine adjuvants continues. In recent decades toll-like-receptor (TLR) agonists have been investigated as potential vaccine adjuvants. In this regard, the majority of the currently investigated TLR agonists are non-protein microbial components such as lipopolysaccharides, oligonucleotides, and lipopeptides. On the other hand, a growing number of studies reveal that TLR signaling and immune responses can be activated by numerous bacterial proteins. However, their potential roles as adjuvants have been somewhat overlooked. Herein, we discuss several such bacterial proteins, which exhibit adjuvant properties, including the activation of TLR signaling, antigen presenting cell maturation, pro-inflammatory cytokine production and adaptive immune response. The protein nature of these TLR agonists present several unique features not shared by non-protein TLR agonists. These properties include the amenability for modifying the structure and function as necessary for optimal immunogenicity and minimal toxicity. Protein adjuvants can be genetically fused to protein antigens which will ensures co-delivery of adjuvant-antigen not only into the same cell but also in the same endocytic cargo leading to more effective activation of innate and adaptive immune response.